Between Studying and New Venturing: Personal Knowledge Management Challenges Through the Lens of Entrepreneurship Undergraduate Students - Najmi Shaumi Mumtaz; Jann Hidajat Tjakraatmadja (Research Synergy Foundation, 2022)
Research to improve entrepreneurship education in higher educational institutions (HEIs) has gained much attention over the past years. Prior studies have thoroughly investigated the challenges of entrepreneurship education based on the providers' and educators’ perspectives. However, the experiences of the students who receive and undergo the process have not received equal attention, especially when investigating the